Optimalisasi Permainan Tradisional Gobak Sodor sebagai Media Pembelajaran Interdisipliner Berbasis Budaya untuk Menguatkan Literasi Numerasi, Literasi Sains, dan Aktivitas Fisik Siswa Sekolah Dasar (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Traditional games are increasingly being abandoned by elementary school children due to the growing use of digital games, reducing physical activity and opportunities for contextual, culture-based learning. This community service program aimed to optimize Gobak Sodor as a culture-based learning medium to strengthen students’ numeracy literacy, scientific literacy, and physical activity at SDN Rejuno 1, Ngawi Regency. The program employed a participatory approach involving needs assessment, school coordination, material development, game demonstrations, guided practice, mentoring, and evaluation. Activities were conducted over six sessions with active participation from teachers and students. The results showed that students understood the rules, applied basic strategies, and recognized mathematical and scientific concepts embedded in the game. Students also demonstrated increased participation, collaboration, sportsmanship, and physical activity during learning. Teachers responded positively to Gobak Sodor as an engaging and contextual learning medium. The program demonstrates that traditional culture-based games can serve as effective interdisciplinary learning media while supporting cultural preservation, strengthening numeracy and scientific literacy, promoting physical activity, and fostering character development. Thus, Gobak Sodor provides a practical and enjoyable approach to integrating cultural values into elementary education.